The effect of broad-crested weir shape on air entrainment - Emiroglu, ME; Baylar, A (Taylor & Francis Ltd, 2003)
Aeration is a mass transfer process between the atmosphere and water. Aeration is used for water quality enhancemert in sewage treatment plants and in polluted rivers and lakes. This can be enhanced by creating turbulence in the water. Plunging overfall jets from weirs are a particular instance of producing such turbulence. This paper investigates flows over broad-crested weirs of different cross-sectional geometry and their effect on the air entrainment rate. It is demonstrated that the air entrainment rate of the 30degrees triangular broad-crested weir is better than for the other broad-crested weirs. Moreover, an empirical correlation predicting air entrainment rate was developed for triangular broad-crested weirs. Good agreement between measured and predicted air entrainment rate values was obtained.
Effet de la forme d'un déversoir à large crête sur l'entraînement d'air
Keywords: aeration; air entrainment; plunging overfall jet; broad-crested weir